Proceedings of the 10th International Conference on Fracture Mechanics of Concrete and Concrete Structures 2019
DOI: 10.21012/fc10.229373
|View full text |Cite
|
Sign up to set email alerts
|

A strength criterion for size effect on quasi-brittle fracture with and without notch

Abstract: This study shows it is sufficient to use only the tensile strength ft to describe the size effect on quasi-brittle fracture behaviors of brittle heterogeneous solids such as rock and concrete. Another essential material property, the average grain size G for rock or the maximum aggregate size dmax for concrete, should be determined separately before fracture analysis. Quasi-brittle fracture behaviors of heterogeneous specimens or structures, small or large and notched or un-notched, can all be described by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…They concluded that the size effect coefficient could be directly calculated from the modulus of rupture [22]. The fracture energy of concrete was size dependent and for non-linear models, two fracture parameters were needed to define the concrete fracture behaviour [23]. The water-cement ratio (w/c) had a significant bearing on the interfacial transition zone between concrete paste and aggregate, thereby affecting the strength of concrete [24].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the size effect coefficient could be directly calculated from the modulus of rupture [22]. The fracture energy of concrete was size dependent and for non-linear models, two fracture parameters were needed to define the concrete fracture behaviour [23]. The water-cement ratio (w/c) had a significant bearing on the interfacial transition zone between concrete paste and aggregate, thereby affecting the strength of concrete [24].…”
Section: Introductionmentioning
confidence: 99%
“…Ince and Cetin (2019) [18] have reported that the fracture parameters of concrete are influenced by compressive strength, maximum aggregate size, water-cement ratio, and aggregate type in testing. Chen Yi et al (2019) [19] have established the sufficiency of the tensile strength of quasi-brittle materials to describe the size effect on test results. Mobasher (2022) [20] has proposed an energy equivalence between the externally imparted energy on the test specimens and the energy dissipated in crack propagation.…”
Section: Introductionmentioning
confidence: 99%